Respuesta :
So you start with 23
for every row up you have -3
equation is
# of boxes= 23- 3x
x representing the number of rows above the bottom
# of boxes= 23- 3x=
23-3(5)= 8
5 for the top row
bottom row has 23
1 row above 23-3(x)=20
2 row above 23-3(x)= 17
3....23-3(x)= 14
4....23-3(x)=11
5...23-3(x)= 8
therefore just add all boxes each row has
23+20+17+14+11+8= 83
I hope this helps
for every row up you have -3
equation is
# of boxes= 23- 3x
x representing the number of rows above the bottom
# of boxes= 23- 3x=
23-3(5)= 8
5 for the top row
bottom row has 23
1 row above 23-3(x)=20
2 row above 23-3(x)= 17
3....23-3(x)= 14
4....23-3(x)=11
5...23-3(x)= 8
therefore just add all boxes each row has
23+20+17+14+11+8= 83
I hope this helps